Secretion pathway of liver IGF-1 via JAK2/STAT3 in chick embryo under the monochromatic light. (2nd January 2016) - Wang, Tuanjie; Dong, Yulan; Wang, Zixu; Cao, Jing; Chen, Yaoxing
Abstract: This study reveals mechanism of monochromatic light on the IGF-1 secretion of chick embryo liver. The chick embryos were incubated and exposed to continuous red, green, blue light or a dark environment. Compared to other light-treated groups, green light increased IGF-1 and melatonin concentrations both in plasma and liver, and Mel1a, Mel1b and Mel1c receptors expressions in liver but decreased p-JAK2, p-STAT3 and ROS in liver. IGF-1 had a positive correlation with melatonin, but a negative relevance with p-JAK2 and p-STAT3. In vitro, the IGF-1 level in the hepatocyte supernatant was enhanced by melatonin with lower p-JAK2/p-STAT3 and ROS levels, which was suppressed by Mel1c antagonist but not Mel1a/Mel1b or Mel1b antagonists. AG490 (JAK/STAT inhibitor) promoted role of melatonin-Mel1c modulated IGF-1 secretion. These results suggest the antioxidant effect of melatonin mediated the green light-enhanced IGF-1 secretion of chick embryo liver through Mel1c receptor to inhibit the JAK2/STAT3 pathway.